Synthesis, characterization and DFT studies of a palladium (ii) complex with bidentate Schiff base ligands - Chakrabarty, Surajit; Bhattacharjee, Shoumik; Rahmani, Rachida; Hussain Sheikh, Afzal; Chouaih, Abdelkader; Hamzaoui, Fodil (International Journal of Advanced Chemistry, 2019)
The N-donor bidentate complexes of Palladium (II) of the type [PdL1Cl2] and [PdL2Cl2] where L1 = N, N'-bis(napthanidal)-1,4-diacetyldihydiimine and L2= N, N'-bis(napthanidal)-1,2-ethylenediimine were synthesized by refluxing of PdCl2 in acetonitrile with ligand L1 and L2. Complexes have been characterized by elemental analysis, conductivity measurement, IR, UV-Vis and 1H-NMR spectroscopy. Full geometry optimization of the ground state of the complex [PdL1Cl2] was carried out using Density Functional Theory (DFT) at B3LYP functional with 6-311G(d, p) basis set for C, N, Cl, H and LANL2DZ basis set for Pd atoms in gas and solvent (DMSO) phases. The calculated geometric and spectral results reproduced the experimental data with well agreement. Theo-retical calculated molecular orbitals (HOMOâ€“LUMO) and their energies have been calculated that suggest charge transfer occurs within the complexes. The HOMO-LUMO energy gap was found 2.6210 eV. The electrophilic and nucleophilic sites are theoretically evaluated by molecular electrostatic potential.Â Â